The Use of Adenosine to Enable Safe Implantation of Transcatheter Tricuspid Valve. (16th November 2017) - Zeniou, Vicki; Chen, Shmuel; Shuvy, Mony; Luria, David; Lotan, Chaim; Danenberg, Haim D.
Abstract : High precision is necessary during percutaneous transcatheter heart valve implantation. The precision of the implantation has been established by increasing the heart rate (usually to 200 beats per minute) to the point of significantly reduced cardiac output and thus minimizing valve movement. Routinely, this tachycardia is induced by rapid pacing. Here we report a case of failure to pace during valve-in-valve (VIV) Edwards Sapien XT implantation in the tricuspid valve position. Transient cardiac arrest was induced by intravenous adenosine injection enabling accurate valve implantation.